1993
DOI: 10.1159/000243975
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Response at Birth in Preterm Newborns

Abstract: We compared the extrauterine adaptation of preterm with term newborn infants, by sequentially measuring plasma catecholamine (CAT) levels at birth and during the first 24 h of life. Twenty-seven preterm appropriate-for-gestational-age (AGA) infants, less than 35 weeks gestation, were compared with 26 healthy near-term AGA infants. Modes of delivery and umbilical arterial pH (mean 7.28) did not differ. Infants with asphyxia, presumed sepsis or hypoglycemia were excluded. CAT (norepinephrine, epinephrine, dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
1
12
0
4
Order By: Relevance
“…Left ventricular output increases twofold to threefold at birth 19 20. This rapid adaption at birth, thought to be triggered by a sudden release of circulating catecholamines,21 22 is also found in preterms 23. However, in 1993, Gill and Weindling24 showed significantly reduced shortening fraction during the first 24 h after birth in a population comparable to ours.…”
Section: Discussionsupporting
confidence: 82%
“…Left ventricular output increases twofold to threefold at birth 19 20. This rapid adaption at birth, thought to be triggered by a sudden release of circulating catecholamines,21 22 is also found in preterms 23. However, in 1993, Gill and Weindling24 showed significantly reduced shortening fraction during the first 24 h after birth in a population comparable to ours.…”
Section: Discussionsupporting
confidence: 82%
“…LAGERCRANTZ and BISTOLETTI [9], GREENOUGH et al [7], PUOLAKKA et al [22] and MEHANDRU [11] found insignificantly lower arterial catecholamine levels in preterm than in term newborn umbilical vessels. By contrast, NEWNHAM et al [12] suggested equal noradrenaline levels and higher adrenaline levels in preterm compared to 40000 20000.…”
Section: Discussionmentioning
confidence: 99%
“…Dies traf allerdings nicht auf die Gruppe der Frühgeborenen zu. Im Gegensatz zu anderen Autoren [7,9,11,12,22] waren alle freien Katecholaminspiegel in der Arteria umbilicalis bei früh-gegenüber reifgeborenen Kindern signifikant erniedrigt. Dies ist eher das Resultat einer verminderten Sekretion als einer erhöhten Degradation von Katecholaminen und könnte durch die zunehmende Reifung des sympathisch-adrenergen Systems erklärbar sein [16] sowie durch die große Anzahl von Kaiserschnitten in der Gruppe von Frühgeborenen.…”
Section: Zusammenfassung Inadäquate Sekretion Von Umbilikalen Plasmakunclassified
“…Das Neugeborene muss nun die Depots zur Energiebereitstellung selbst mobilisieren. Beim gesunden reifen Neugeborenen kommt es zu einem akuten Anstieg der Blutkonzentrationen von Epinephrin, Norepinephrin, Glukagon und Abfall des Insulins [10][11][12] . Diese Hormone stimulieren Glykogen aus der Leber [13] [14,15] .…”
Section: Postpartaler Glukosemetabolismusunclassified